Conditions necessary to maintain work-life balance of employees - in the light of the research results = Warunki zachowania równowagi między pracą zawodową a życiem prywatnym pracowników - w świetle wyników badań - Stankiewicz, Janina; Bortnowska, Hanna; Łychmus, Patrycja (Zielona Góra: Faculty of Economics and Management Press)
The article presents the results of research concerning work life balance of employees of enterprises located in lubuskie voivodeship. The working conditions provided by employers were analyzed. The authors of research checked whether they favor, according to the respondents, the homeostasis between work and private life. The results showed some deficits in this area. This led to reflection on the potential remedial actions which can be applied in the organization, such as a policy of "family friendly employment".
Keywords: praca zawodowa; życie prywatne pracowników; zachowanie równowagi; zatrudnienie przyjazne rodzinie; professional work; private life of employees; family friendly employment